2018
DOI: 10.1080/22243682.2018.1522599
|View full text |Cite
|
Sign up to set email alerts
|

Development of new hybridPhoenix pusilla/carbon/fish bone filler reinforced polymer composites

Abstract: Designing new eco-friendly fibers enable the creation of an alternative resource for many applications, specifically within the field of polymeric composites. This paper details the fabrication of hybrid epoxy composites comprising natural fiber, Phoenix Pusilla plant dry leaves which belong to the family of date palm and nanofillers made from the fish bones, which has been explored for the first time. ASTM standards provided the guidelines for the preparation of samples and mechanical measurements. The mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 15 publications
0
45
0
Order By: Relevance
“…The TFBPs-loaded epoxy composites showed lower void fractions compared to the FBP loaded epoxy composites for the entrapment of less air. [14] Higher void fraction in composites may be found for the inhomogeneous dispersion of the FBPs. Because poor dispersion may allow to entrap more mechanical air into composites.…”
Section: Void Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TFBPs-loaded epoxy composites showed lower void fractions compared to the FBP loaded epoxy composites for the entrapment of less air. [14] Higher void fraction in composites may be found for the inhomogeneous dispersion of the FBPs. Because poor dispersion may allow to entrap more mechanical air into composites.…”
Section: Void Fractionmentioning
confidence: 99%
“…[12][13][14][15][16] Among the natural fillers, fishbone has already been used in both thermoplastic and thermosetting polymers. [14,17] In a recent study, the fishbone particles (FBPs) along with Phoenix pusilla plant dry leaves showed that they could improve the tensile strength, flexural strength, and hardness by 22.5, 200, 100, and 15.2%, respectively. The interactions between the fillers and the epoxy were highlighted in details in the previous article.…”
mentioning
confidence: 99%
“…The nano-modified mixed-matrix SiO2/Al2O3 showed a controlled rate of wear as well as reduction in friction coefficient. Various fillers of biochar particles derived from rice husk (Richard, Rajadurai, & Manikandan, 2016), fishbone (Abhishek et al, 2018), hemp hurds, alfalfa, and grape stem (Battegazzore, Noori, & Frache, 2019), lignocellulosic wood (Kumar, Kumar, & Bhowmik, 2018), thyme herbs (Montanes, Garcia-Sanoguera, Segui, Fenollar, & Boronat, 2018), rice husk ash and siliceous earth-Sillitin Z 86 (Pongdong, Kummerlöwe, Vennemann, Thitithammawong, & Nakason, 2018) have been added to various polymer matrices to reduce the materials (polymers) cost, enhance important properties of the resultant composites, such as mechanical, dimensional and thermal stability. This work explored the possibility of using Polyalthia longifolia (Mast tree) seed powder as a reinforcement in vinyl ester resin for the development of partially biodegradable composite material.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, Kevlar-reinforced ultra-high molecular weight polyethylene (UHMWPE) composite is finding its potential in body armor and stab resistance applications due to their unique properties such as flexibility, high strength to weight ratio, and excellent fracture toughness. [1][2][3][4] Kevlar-reinforced UHMWPE is better alternative for traditional materials such as cast iron, steel, wrought steel, hardened steel for body armor, and stab resistance applications. The limitations of traditional materials were heavy weight, challenging manufacturing, rigidity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…57 Contemporary body armor materials are ceramics, metal matrix composites, and fiber-reinforced composites. 812 Literature reveals the suitability of Kevlar®-reinforced composite for body armor applications using a 9 mm bullet. 13 Ultra-high molecular weight polyethylene is also a lightweight polymer material, which plays a vital role in the energy absorption mechanism.…”
Section: Introductionmentioning
confidence: 99%